2022
DOI: 10.1186/s12903-022-02216-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of phytochemical-filled microcapsules with antifungal activity on material properties and dimensional accuracy of denture base resin for three-dimensional printing

Abstract: Background Studies on the material properties and dimensional accuracy of three-dimensionally (3D) printed denture base containing microcapsules with antifungal phytochemicals are lacking. Methods Two types of phytochemicals (phytoncide A and B) with antifungal activity were microencapsulated. The 3D-printed denture base specimens with minimum and maximum effective concentrations of microcapsules (6 and 8 wt% for phytoncide A; 15 and 25 wt% for phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 43 publications
3
15
0
Order By: Relevance
“…albicans adhesion or proliferation of colonies on the surface of 3D-printed denture base. The presence of phytochemical-filled microcapsules significantly reduced fungal cell adhesion and inhibited cell proliferation on the surfaces of denture base, which was consistent with previous studies [ 21 , 22 ]. At a certain concentration of phytochemical-filled microcapsules, the 3D-printed denture base showed significant antifungal activity against C .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…albicans adhesion or proliferation of colonies on the surface of 3D-printed denture base. The presence of phytochemical-filled microcapsules significantly reduced fungal cell adhesion and inhibited cell proliferation on the surfaces of denture base, which was consistent with previous studies [ 21 , 22 ]. At a certain concentration of phytochemical-filled microcapsules, the 3D-printed denture base showed significant antifungal activity against C .…”
Section: Discussionsupporting
confidence: 92%
“…To fabricate the phytochemical-filled microcapsules, a phytoncide oil was extracted from Pinus densiflora (Cleandiox Ltd., Gyeonggi-do, Korea) and incorporated into microcapsules using melamine-based polymers, as reported in a previous study [ 21 ]. The phytochemical-filled microcapsules were mixed with a 3D-printable denture-base resin (NextDent Denture 3D+, Vertex Dental BV, Soesterberg, Netherlands), at a concentration of 5wt% [ 22 ]. A dispersant (DISPERBYK-111, BYK-Chemie, Wesel, Germany) was also added at 20wt% of the mass (g) of microcapsules to the microcapsule-printable resin mixture for uniform dispersion.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the antifungal properties, DBR containing 6 wt.% of type A and 15 wt.% of type B phytoncide microcapsules revealed a significant reduction against C. albicans growth [ 65 ]. The same authors in another study demonstrated that incorporating 6 wt.% of type A and 15 wt.% of type B phytoncide microcapsules into DBR was associated with a significant reduction in the flexural strength, elastic modulus, and microhardness of the DBR materials [ 66 ]. Such observations may suggest the need for more characterization of this compound to be functionalized into DBRs without compromising the mechanical properties.…”
Section: Methods Used For Tuning Bioactive and Antimicrobial Dbr Mate...mentioning
confidence: 99%
“…DBR containing 6 wt.% of type A and 15 wt.% of type B phytoncide microcapsules revealed a significant reduction against C. albicans growth [ 65 ], but the mechanical and physical properties were negatively affected [ 66 ]…”
Section: Figurementioning
confidence: 99%